PENGARUH FLASH SALE DAN FOMO TERHADAP ONLINE SHOPPING BEHAVIOR MELALUI IMPULSIVE BUYING PADA MAHASISWA STIE NU - Uswatun Khasanah; Yulia Rahmah; Nur Samsi; Reza Rifanda Dwi Cahya Maula (Sekolah Tinggi Ilmu Ekonomi NU Trate Gresik, 2025)
ABSTRACK This study aims to analyze the influence of flash sales and fear of missing out (FoMO) on online shopping behavior through impulsive buying among students of STIE NU Trate Gresik. This research uses a quantitative approach with a survey method by distributing questionnaires to 71 respondents who are active students. The data analysis technique used is Partial Least Squares (PLS) with the help of WarpPLS 7.0 software. The research results show that FoMO has a positive and significant effect on impulsive buying, while flash sales do not have a significant effect on impulsive buying. Impulsive buying has a positive and significant effect on online shopping behavior. Additionally, FoMO also has an indirect effect on online shopping behavior through impulsive buying, while the indirect effect of flash sales through impulsive buying on online shopping behavior is not significant. This research shows that FoMO is a key factor driving impulsive buying and online shopping behavior among students, especially students of STIE NU Trate Gresik.